Prospects for Collaborative Industrial Doctoral Education in Russia - V. A. Teslenko; R. M. Melnikov (Высшее образование в России)
The article proposes recommendations on the development of collaborative industrial doctoral education in Russian conditions considering international experience and provides a justification for the Russian high-tech companies’ demand for the competences of graduates of the collaborative doctoral programs. The regression analysis of patent and innovation activity indicators of Russian high-tech companies on the share of employed with academic degrees showed that successful graduates of Russian doctoral schools with specialization in technical sciences have an option to apply their research competences in the real sector of the economy. This determines the need to develop and put into practice specialized doctoral programs aimed at training scientific and engineering personnel for high-tech companies in the form of collaboration with industrial partners. Such programs can be implemented using the industrial PhD model, which is based on a research project in the interests of the employer with dual scientific supervision and funding of the study at the expense of the employer. Collaborative industrial doctoral programs require a longer training duration than traditional academic doctoral programs, as well as a reduced classroom load, especially concerning pedagogical and general disciplines. Grants, tax credits and preferential treatment for procurement by large state-owned companies can be used to encourage Russian high-tech companies with high research and development costs to become industrial partners of doctoral schools.